Weak hydrogen bonding and fluorous interactions in the chloride and bromide salts of 4‐[(2, 2, 3, 3‐tetrafluoropropoxy)methyl]pyridinium. Issue 4 (1st April 2017) - Lu, Norman; Wei, Rong-Jyun; Lin, Kwan-Yu; Alagesan, Mani; Wen, Yuh-Sheng; Liu, Ling-Kang
Abstract : The halide anions in 4‐[(2, 2, 3, 3‐tetrafluoropropoxy)methyl]pyridinium chloride and bromide accept four hydrogen bonds from N—H, ortho ‐C—H and CF2 —H groups. Two cations and two anions form a centrosymmetric dimeric building block, utilizing complimentary N—H… X …H—C sp 3 connections. These dimers are further crosslinked, utilizing another complimentary C sp 2 —H… X …H—C sp 2 connection. Abstract : Neutralization of 4‐[(2, 2, 3, 3‐tetrafluoropropoxy)methyl]pyridine with hydrohalo acids H X ( X = Cl and Br) yielded the pyridinium salts 4‐[(2, 2, 3, 3‐tetrafluoropropoxy)methyl]pyridinium chloride, C9 H10 F4 NO + ·Cl −, (1), and 4‐[(2, 2, 3, 3‐tetrafluoropropoxy)methyl]pyridinium bromide, C9 H10 F4 NO + ·Br −, (2), both carrying a fluorous side chain at the para position of the pyridinium ring. Single‐crystal X‐ray diffraction techniques revealed that (1) and (2) are isomorphous. The halide anions accept four hydrogen bonds from N—H, ortho ‐C—H and CF2 —H groups. Two cations and two anions form a centrosymmetric dimeric building block, utilizing complimentary N—H… X …H—C sp 3 connections. These dimers are further crosslinked, utilizing another complimentary C sp 2 —H… X …H—C sp 2 connection. The pyridinium rings are π‐stacked, forming columns running parallel to the a axis that make angles of ca 44–45° with the normal to the pyridinium plane. There are also supramolecular C—H…F—C interactions, namely bifurcated C—H…F and bifurcated C—F…H interactions; additionally, one type II C—F…F—C halogen bond has been observed.